SYNTHESIS, CHARACTERIZATION, AND ANTIBACTERIAL ACTIVITY TEST OF CURCUMIN ANALOG MONOCARBONYL COMPOUNDS - Rahmawati, Ismi
The relatively high intensity of antibiotic use raises various problems, especially bacterial resistance to antibiotics. Curcumin or 1.7-bis-(4-hydroxy-3- methoxyphenyl)-1,6-heptadiene-3,5-dion is a natural yellow pigment derived from the rhizome of the Curcuma longa (Zingiberaceae) plant. Curcumin has antimicrobial activity against several Gram positive and Gram negative bacteria. Antibacterial working mechanism of curcumin influences cell membrane permeability and peptidoglycan biosynthesis. The disadvantage of curcumin is that its bioavailability is very low, very hydrophobic, and unstable by the influence of light and pH above 7.4. The best approach in modifying the curcumin molecule is the synthesis of the monocarbonyl analog by converting ?-diketone to ?-monoceton. The halogen groups Cl and Br are known to be good enough in increasing antibacterial activity. This study aims to synthesize and characterize analogous curcumin monocarbonyl compounds with Cl and Br halogen functional groups. The synthesized compounds were then tested for antibacterial activity against resistant and non-resistant bacteria. The study began by synthesizing 6 analog compounds of monocarbonyl curcumin: 2,6-bis(5’-chloro-2’-furanyl)cyclohexanone (26ClH); 2.5-bis(5’-chloro-2’-furanyl cyclopentaone (25ClP); 1.5-di(5’chloro-2’furanyl)-1-4-pentadien-3-one (15ClA); 2,6-bis(5’-bromo-2’-furanyl)cyclohexanone (26BrH); 2.5-bis(5’-bromo-2’- furanyl) cyclopentaone (25BrP); 1,5-di(5’chloro-2’furanyl)-1-4-pentadien-3-one (15BrA) using the aldol condensation method in various conditions. The synthesis was carried out by reacting ketones in a 30% NaOH catalyst. Compounds 26ClH and 26BrH use cyclohexanone, 25ClP and 25BrP using cyclopentanone and 15ClA and 15BrA using acetone. The solutions then reacted with furfuraldehydes that had halogen funtional groups. 26ClH, 26ClP, and 15ClA compunds used 2,5- chloro-furfuraldehyde, and 26BrH, 25BrP, and 15BrA compounds used 2,5- bromo-furfuraldehyde. The synthesis results showed that the highest yield of 15ClA compound was 85.57 ± 2.54% which was not significantly different from 15BrA compound of 83.47 ± 1.08%. This showed that it was acetone as a starting compound which causes high yields in the synthesis results. The synthesis results were characterized by thin layer chromatography, melting distance, spectrophotometric GC-MS, spectrophotometric FTIR, 1 HNMR 7 spectrophotometry and 13 CNMR spectrophotometry. The results of TLC silica gel GF254 showed that all compounds produced one spot with a combination of nhexane and chloroform with various comparisons. The melting distance of the six compounds has a small range between 0.3-2.3 o C. The results of gas chromatography (KG) of all target compounds have a percentage of area under the curve of 82.44-100%. The results of mass spectrophotometry (MS) at the peak of the retention time showed m / z which corresponds to the molecular weight of the target compound. The existence of 2 Cl atoms on the target compound 26ClH, 25ClP and 15ClA is indicated by the typical Cl isotope abundance pattern, namely: M +: M + 2: M + 4 = 9: 6: 1. This can also be seen in the results of MS for compounds 26BrH, 25BrP and 15BrA showing 2 Br atoms with typical Br isotope abundance patterns, namely: M +: M + 2: M + 4 = 10: 19: 9. The results of the analysis of FTIR spectra showed that all the target compounds had a ??- unsaturated carbonyl structure. This is indicated by the absorption of the carbonyl group (C=O) which has been conjugated with a C=C alkene double bond. The other absorbed groups are alkyl groups (-CH2-), alkene groups (C=C) aromatic, ether groups (C-O-C) and carbon bonds with halogens (C-X). Spectrometric analysis of 1 H NMR and 13 C NMR shows the presence of signal regions that correspond to the type of proton H and the target compound carbon. The target compound has a symmetrical structure indicated by the type of H and carbon protons that are identical. The characterization results show the character of the structure that matches the target compound All compounds were tested for antibacterial activity by Kirby-Bauer diffusion method on Gram negative bacteria Salmonella thypi ATCC 13311, Escherichia coli ATCC 25922, Klebsiella ATCC 10031 pneumonia, Pseudomonas aeruginosa ATCC 27853, and Gram positive bacteria Stapylococcus aureus ATCC 25923, Streptococcus mutant ATCC 2517, Bacillus subtillis ATCC 6633, Methicillin- Resistant Staphylococcus aureus (MRSA) resistant bacteria, the resistant Staphylococcus aureus isolated from clinical patients. The diameter of inhibition was analyzed statistically by one-way ANOVA using the Tukey model Post Hoc Test with a significance value of 0.05. The results showed that 15ClA compound had a potential activity to be developed in several Gram negative bacteria and 15BrA compounds in positive Gram bacteria. The difference in activity is caused by different cell wall components of the two types of bacteria. The overall activity test results showed that compound 15ClA had the most active activity in the bacteria P. aeruginosa. The test results using the macrodilution method showed that the minimum inhibitory concentration of compound 15ClA was 2.4 ?g / mL against P. aeruginosa. The antibacterial work location of the 15ClA compound was observed by scanning electron microscope (SEM) and transmission electron microscopy (TEM). SEM results of intact bacterial cells showed a compact bacterial morphology of rod-shaped with smooth surface, without spot. SEM results with the treatment of 15ClA compound showed damage to the cell wall surface marked by black spots in SEM and TEM. Other cell observations show cells that shrink, fold and size reduction of bacteria which are indication of lysis of cell contents without cell wall damage. The location of 8 antibacterial cells works on the cell surface (peptidoglycan and outer membrane) of bacteria and internal membranes. The effect of 15ClA compounds on the biosynthesis of peptidoglycan bacterial cell walls has been predicted by docking. The results of the prediction of the enzyme UDP-N-acetylglucosamine-1-carboxyvinyltransferase (MurA) as molecular targets. Molecular docking studies were carried out with Vina PyRx 0.8 software. The results of molecular docking study showed that 15ClA compounds can interact with target proteins with an affinity of -7.2. In vitro, the 15ClA compound showed better activity than curcumin. Curcumin has a phenol group and polar OH group which can facilitate the occurrence of hydrogen bonds with the target receptors. This is what causes curcumin difficulty in penetrating into bacterial cells which causes decreased activity. The effect of compound 15ClA on bacterial cell membranes was proven by detection of increased levels of nucleic acids, proteins and metal ions in the culture supernatant. The supernatant was analyzed using UV-Vis spectrophotometry at a wavelength of 260 nm for nucleic acids and 280 nm for protein. The concentration of Na +, K + and Mg2 + metal ions was analyzed by Atomic Absorption Spectroscopy (AAS). The absorbance of UV-Vis spectrophotometry showed an increase in nucleic acid and protein concentrations, compared with negative controls and the addition of the concentration of the test compound. Changes in cell membrane permeability due to contact with the test compound cause the number of Na +, K + and Mg2 + ions outside the cell to increase. The results of the study concluded that six target compounds could be synthesized by aldol condensation reaction mechanism using 30% NaOH m/v base catalyst in room temperature and 40 o C. The highest yield is found in 15ClA compound (85,57±1,31%) and 15BrA (83,47±1,08%). The results of the characterization of the six target compounds matched the target compounds. All six compounds had better antibacterial activity than curcumin. The compound 15ClA has potential antibacterial activity on Gram negative E. coli, K. pneumonia and P. aeruginosa. The compound 15BrA has potential antibacterial activity on Gram positive S. aureus and B. subtilis. The compound 15ClA is the compound that has the most active activity on P. aeruginosa with minimum bacterisid concentration 4,9?g/mL. The antibacterial mechanism of compound 15ClA against P. aeruginosa might cause the biosynthesis of cell peptidoglycan and cell membrane leakage.